Impact of SARS-CoV-2 infection in pregnant women and their babies: clinical and epidemiological features - María José Vidal; Èrica Martínez-Solanas; Sergi Mendoza; Núria Sala; Mireia Jané; Jacobo Mendioroz; Pilar Ciruela (Elsevier, 2023)
Objective: Assess the risk associated with COVID-19 in pregnant women on maternal and neonatal outcomes in Catalonia (Spain) in 2020, before the beginning of COVID-19 vaccination campaign. Method: Cross-sectional descriptive study with all pregnant women (41,560) and their live newborns (42,097) (1st March to 31st December 2020). Women were classified: positive and negative COVID-19 diagnosis during pregnancy. The outcomes analysed were complications during pregnancy, gestational age, admission of newborns to neonatal intensive care unit (NICU) and birth weight. Associations among positive COVID-19 and maternal and infant variables were measured with logistic regression models. Results were expressed as odds ratios and 95% confidence intervals. Models were adjusted for nationality, maternal age, socioeconomic status, type of pregnancy and type of centre where the delivery occurred (public or private management hospital). Results: A total of 696 women (1.7%) were diagnosed with COVID-19 during pregnancy. Women with COVID-19 were 4.37 times more likely to have complications during pregnancy (4.37; 3.52-5.40). A total of 713 newborns (1.7%) were from mothers with COVID-19. A positive diagnosis of COVID-19 increased the risk of preterm birth (1.41; 1.03-1.89), admission to NICU (1.40; 1.06-1.82) and low birth weight (1.35; 0.99-1.80) in babies. Conclusions: Pregnant women with COVID-19 had higher risk of developing complications during pregnancy and their newborns were more likely to be admitted to NICU and had prematurity. Resumen: Objetivo: Evaluar el riesgo asociado de COVID-19 y los resultados en mujeres embarazadas y sus recién nacidos en Cataluña (España) antes del inicio de la campaña de vacunación. Método: Estudio descriptivo transversal de mujeres gestantes (41.560) y sus recién nacidos (42.097) (del 1 de marzo al 31 de diciembre de 2020). Las gestantes fueron clasificadas según diagnóstico COVID-19 positivo o negativo durante el embarazo. Los resultados analizados fueron complicaciones gestacionales, semana gestacional, ingreso del recién nacido en la unidad de cuidados intensivos neonatales (UCIN) y bajo peso al nacer. Las asociaciones entre COVID-19 positivo y variables maternas y perinatales se midieron con regresión logística. Los resultados se expresaron con odds ratio e intervalo de confianza del 95%. Los modelos se ajustaron por nacionalidad, edad materna, nivel socioeconómico, tipo de embarazo y titularidad (pública o privada) del hospital donde se dio a luz. Resultados: Un total de 696 gestantes (1,7%) fueron diagnosticadas de COVID-19 durante el embarazo. Las gestantes con COVID-19 presentaron 4,37 veces mayor probabilidad de tener complicaciones durante el embarazo (4,37; 3,52-5,40). Hubo 713 recién nacidos (1,7%) de gestantes con COVID-19. El diagnóstico positivo de COVID-19 incrementó el riesgo de prematuridad (1,41; 1,03-1,89), ingreso en UCIN (1,40; 1,06-1,82) y bajo peso al nacer (1,35; 0,99-1,80) de los recién nacidos. Conclusiones: Las gestantes con COVID-19 presentaron mayor riesgo de desarrollar complicaciones durante el embarazo y sus hijos tuvieron mayor probabilidad de ingreso en la UCIN y de prematuridad.